The Influence of Quality of Work Life and Presence of Career Calling on Intrinsic Work Motivation among Teachers in Private Secondary School X and Y - Salsabila, Maula Rizka; Yuliawati, Livia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This study aims to explore the influence of Quality of Work Life and Presence of Career Calling on teachers' intrinsic work motivation in private secondary schools X and Y. Quality of Work Life refers to working conditions that include aspects of work-life balance, social support, recognition of contributions, and a supportive work environment, while Presence of Career Calling reflects the extent to which teachers perceive their work as a calling that has deep purpose and meaning. This research is expected to provide valuable insights for school management in developing strategies to increase teachers' intrinsic motivation, so as to contribute to improving the quality of education in both schools. This study aims to determine the effect of Quality of Work Life and Career Vocation on teachers' intrinsic work motivation in two private secondary schools. Using quantitative methods and total population study techniques, this study obtained the participation of 87 teachers as research samples. Data collection was conducted through an online survey using a validated questionnaire. The results of this study showed a significant effect of Presence of Career Calling on intrinsic work motivation, while Quality of Work Life did not have a significant effect on intrinsic work motivation. This finding is consistent with previous research regarding calling variables increasing intrinsic motivation but differs in the case of Quality of Work Life which shows no effect.